Players’ and coaches’ perceptions of players’ mental health help-seeking process in elite level football - Hyvönen, Laura (2024)
Mental health among athletes has been a discussed topic in the media in the past years and multiple athletes have started sharing public stories about their mental health problems. The topic has also gained more and more interest in the area of research in recent years. This Master’s thesis concentrated on finding out the perceptions of the players’ help-seeking process in elite level football. The purpose of the study was to examine how players and coaches in Kansallinen Liiga perceived the current mental health help-seeking process for players, what were their needs for the process at the moment, and how the support system could be developed in the future if needed. Additionally, perspectives about responsibilities to offer support were asked.